Options of Using Oxford Happiness Survey of Latgale Inhabitants Happiness Structural Studies - Kalvāns, Ēriks (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The problem of happiness and psychological well-being is one of the fundamental problems in psychology; therefore it maintains the interest in itself throughout the history of the science of psychology. The demand for the research on the phenomenon of happiness has significantly increased in the world, and that is caused by the increase in the number of everyday stress situations, the increase of complexity of designing one’s personal life, more complex choices of directions in life, socialization difficulties, significant changes of social norms and values. A number of studies confirmed the link between happiness and the socio-economic conditions in the country. The low standard of living of Latgale’s inhabitants resulted in a fast decline of the number of inhabitants in the region. The unemployment rate in Latgale is the largest rate of unemployment in Latvia. These facts raise the question of choice of valid methodology  of happiness studies that meet the Latgale cultural and economic characteristics. The aim of this article is to describe options of using Oxford happiness survey of Latgale inhabitants  happiness studies and cultural adaptation of this methodology.